Keeping up with the class: A critical discourse analysis of teacher interactions in a co-teaching context. Issue 1 (2nd January 2016) - Ashton, Jennifer Randhare
Abstract : Co-teaching is a model of inclusive instruction that has become increasingly popular throughout schools as a way to meet the needs of students with disabilities in general education settings. Despite being the focus of significant educational research for more than two decades, traditional deficit discourses of disability persist in educational settings and have been found to impede inclusive education efforts. This study draws from the critical theoretical field of Disability Studies in Education (DSE) and methodological foundations of Critical Discourse Analysis (CDA) to analyse the discursive interactions of two middle school co-teachers in a nominally inclusive context. Findings suggest that pedagogy and interactions with students privileged 'keeping up' with the pace of the standardised general education curriculum, which resulted in inequity and marginalisation of students with disabilities in the co-taught classroom.